THE EFFECTS OF LEADERSHIP AND JOB INVOLVEMENT ON THE PERFORMANCE OF EMPLOYEE ON PT. YAKIN INDAH LESTARI PEKANBARU - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2025)
This study aims to determine the leadership style and work involvement of employee performance at PT. Yakin Indah Lestari Pekanbaru which is engaged in bicycle distributors. This analysis is based on 34 respondents who are all employees of PT. Sure Indah Lestari Pekanbaru. The method of data collection carried out in this analysis is through questionnaires while to discuss how leadership style and work involvement affect employee performance at PT. Yakin Indah Lestari Pekanbaru is by using the descriptive analysis method. The hypothesis in this study is that leadership style and work involvement affect employee performance at PT. Sure Indah Lestari Pekanbaru. In hypothesis testing, multiple regression analysis, determination coefficient test, simultaneous test and partial test are used with the help of the SPSS 19.0 program. Based on the results of this study, it is known that leadership style and work involvement simultaneously have a significant effect on employee performance at PT. Yakin Indah Lestari Pekanbaru with a coefficient of determination of 69.9%. The results of the partial test show that leadership style has a significant effect on employee performance at PT. Yakin Indah Lestari Pekanbaru and work involvement have a significant effect on employee performance at PT. Sure Indah Lestari Pekanbaru. This research suggests that leaders further increase their intellectual stimulation and provide good guidance for employees This research also suggests that leaders more often involve employees in the implementation of duties, Provide an opportunity to express their ideas, so that each employee feels valued by the company.